Pelatihan Quick English Learning Course (QELC) di Pasar Tumpah Pringgondani Teritip - Husien, Nanie; Nafiz, Muhammad (ANDIL Mulawarman Journal of Community Engagement, 2024)
Engslih Learning at the Pringgondani market is an important initiative because the Pasar Tumpah Pringgondani is a traditional market with unique characteristics that set it apart from other markets. The uniqueness of the Pringgondani traditional market has become a new icon that blends the concept of traditional food, customs and traditions, as well as a distinctive traditional atmosphere. This provides a unique and interesting tourist experience, which has led to an increase in visitors, not only from within the country but also internationally. Therefore, adequate communication skills, particularly in English, are crucial for business owners and workers at the Pringgondani pop-up market. The Quick English Learning Course (QELC) training provided to business owners and workers at the Pasar Tumpah Pringgondani by the teaching team was highly appreciated by the management and was successful, as evidenced by the improvement in English proficiency among the training participants.